Die Erde, der Mensch und das Soziale: Zur Transformation gesellschaftlicher Naturverhältnisse im Anthropozän - Laux, Henning; Henkel, Anna (transcript, 2018)
The sociologically reflected and socio-politically effective idea of the »anthropocene«, which was created by the sciences, is linked to a worldview that is based on a threefold paradigm shift: Firstly, the Earth is no longer considered a given fact but rather an endangered planet. Secondly, man (again) is placed into the center of the world because humans seem to be the relevant factor when it comes to the irreversible changes and destruction of our planet. And thirdly, the border between society and biophysics is becoming blurred. The contributions in this book therefore explore the scientific challenges, political disputes and social effects that go hand in hand with the posited beginning of the Age of the anthropocene.